Tract-Based Spatial Statistics: Application to Mild Cognitive Impairment. (12th May 2014) - Wai, Yau-Yau; Hsu, Wen-Chuin; Fung, Hon-Chung; Lee, Jiann-Der; Chan, Hsiao-Lung; Tsai, Ming-Lun; Lin, Yu-Chun; Wu, Yih-Ru; Ying, Leslie; Wang, Jiun-Jie
Abstract : Rationale and Objectives . The primary objective of the current investigation was to characterize white matter integrity in different subtypes of mild cognitive impairment (MCI) using tract-based spatial statistics of diffusion tensor imaging. Materials and Methods . The study participants were divided into 4 groups of 30 subjects each as follows: cognitively healthy controls, amnestic MCI, dysexecutive MCI, and Alzheimer's disease (AD). All subjects underwent a comprehensive neuropsychological assessment, apolipoprotein E genotyping, and 3-tesla MRI. The diffusion tensor was reconstructed and then analyzed using tract-based spatial statistics. The changes in brain white matter tracts were also examined according to the apolipoprotein E ε 4 status. Results . Compared with controls, amnestic MCI patients showed significant differences in the cerebral white matter, where changes were consistently detectable in the frontal and parietal lobes. We found a moderate impact of the apolipoprotein E ε 4 status on the extent of white matter disruption in the amnestic MCI group. Patients with AD exhibited similar but more extensive alterations, while no significant changes were observed in dysexecutive MCI patients. Conclusion . The results from this study indicate that amnestic MCI is the most likely precursor to AD as both conditions share significant white matter damage. By contrast, dysexecutive MCI seems to be characterized by a distinct pathogenesis.